A new platygastrid wasp from Florida (Hymenoptera: Platygastridae) - Macgown, Matthew W.; Evans, Gregory A. (Zootaxa, 2003)
Synopeas russelli MacGown, n. sp. is described and illustrated from specimens collected in Orlando, Florida. Numerous specimens of both sexes were collected in a malaise trap and others swept from coastalplain goldenaster, Chrysopsis scabrella, an indicator species for Florida scrub.